2018
DOI: 10.1063/1.5029857
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced interfacial Dzyaloshinskii-Moriya interaction and isolated skyrmions in the inversion-symmetry-broken Ru/Co/W/Ru films

Abstract: An enhancement of the spin-orbit effects arising on an interface between a ferromagnet (FM) and a heavy metal (HM) is possible through the strong breaking of the structural inversion symmetry in the layered films. Here, we show that an introduction of an ultrathin W interlayer between Co and Ru in Ru/Co/Ru films enables to preserve perpendicular magnetic anisotropy (PMA) and simultaneously induce a large interfacial Dzyaloshinskii-Moriya interaction (iDMI). The study of the spin-wave propagation in the Damon-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 33 publications
0
24
0
1
Order By: Relevance
“…All these asdeposited films had in-plane anisotropy only and minimal surface roughness. Recently, it has been shown that Pt, Ta, and Ru have a negative IDMI at the bottom interface, leading to partial cancellation of the effective IDMI (D eff ) if a ferromagnet layer is sandwiched between them 46,47 . We defined by BLS that these three reference samples have negative effective values of the IDMI: D eff = −0.83, −0.48, and −0.34 erg/cm 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…All these asdeposited films had in-plane anisotropy only and minimal surface roughness. Recently, it has been shown that Pt, Ta, and Ru have a negative IDMI at the bottom interface, leading to partial cancellation of the effective IDMI (D eff ) if a ferromagnet layer is sandwiched between them 46,47 . We defined by BLS that these three reference samples have negative effective values of the IDMI: D eff = −0.83, −0.48, and −0.34 erg/cm 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the uniaxial-anisotropy constant can be too small to maintain the PMA or be as large as 10 6 J/m 3 . The DMI constant can be between 0 and 3 mJ/m 2 [25], depending on the composition and thickness of the HM or FM layers and the annealing treatment. All the parameters used in our simulation are in an experimentally achievable range.…”
Section: Modelmentioning
confidence: 99%
“…Therefore, it is enough that one HM layer has spin Hall effect [18]. Some compositions of HM/FM satisfy the above requirement, such as Pt/Co and Co/Ir/Pt [26], and W/Co and Co/Ru/W [25].…”
Section: Modelmentioning
confidence: 99%
“…Зачастую в качестве тяжелого металла используют благородные металлы, такие как Pt, Pd, Ru и др., в этом случае пленки обладают повышенной коррозионной стойкостью. Помимо этого, благодаря наличию межфазного обменного взаимодействия Дзялошинского−Мория [3] между атомами металлов, в таких пленках возможно существование стабильных при комнатной температуре наноразмерных магнитных структур -скирмионов [4]. Применение пленок ферромагнетик/тяжелый металл в ряде приборов спинтроники, например, слоев CoPt в конструкции спинового светоизлучающего диода [5], позволяет существенно снизить диапазон рабочих магнитных полей вплоть до возможности функционирования прибора без приложения внешнего магнитного поля за счет использования остаточной намагниченности материала.…”
Section: Introductionunclassified